Pelatihan Budidaya Maggot BSF bagi PKK dalam Pengelolaan Sampah Organik - Elga Widiastuti Widiastuti; Destina Anja K; Elga Widiastuti; Fatma Mia A; Septia Nuraini; Alfath Rozaqi; Titis Gayuh P.A; Dafin Eko P; Muhammad Irvan A; Kusuma Wardani; Anifah Anifah; Hanifah Khoirunida; Amining Rahmasiwi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Household organic waste, particularly food waste, can cause environmental pollution if not properly managed. This community service program in Tlingsing Village, Cawas District, Klaten Regency, aimed to improve PKK members’ knowledge of Black Soldier Fly (BSF) maggot cultivation as an alternative method for managing organic waste. The program consisted of coordination with the village government, independent maggot cultivation by the KKN team at the community service post as a technical trial, and training for 45 PKK members involving material delivery, demonstrations, feeding practices, discussions, and distribution of maggot starter cultures. Evaluation was conducted descriptively and qualitatively through participatory observation. The results indicated improved participants’ understanding of waste bioconversion, cultivation techniques, the use of maggots as an alternative feed, frass as organic fertilizer, and the economic potential of maggot cultivation. Participants’ enthusiasm also indicated their potential to independently practice maggot cultivation at home. The sequential experiential learning model, involving facilitator trials before community training, offers a promising approach for similar community service programs.. Keywords: Black Soldier Fly (BSF) maggots, organic waste, Family Welfare Empowerment (PKK), bioconversion, community service.